Auricular erythermalgia showing excellent response to itraconazole: a case report - Yan-Ting Ye; Jing-Fa Lu; Hui-Hui Wu; Juan-Hua Liu; Yu-Kun Zhao; Di-Qing Luo (SAGE Publishing, 2022)
Erythermalgia, a rare painful disorder, is characterized by recurrent pain attacking, warmth, and erythema that mainly involves the distal extremities. Red ear syndrome shares similar clinical features of erythermalgia afflicting the external ear with unilateral/bilateral distribution. The treatments of both diseases are still difficult without controlled therapeutics available up to date. A 12-year-old boy was referred because of 3 years of recurrent attacking of painful erythema and warmth that involved the ears alone, the episodes occurred several times daily with duration of dozens of minutes to hours for each flare. The symptoms could be relieved by cold water and triggered by heat stimuli as well as exciting and movement, and showed mild response to gabapentin, celecoxib, and topical lidocaine compounds in combination, but moderate to blocking injection of botulinum toxin to nervus auricularis magnus. However, systemic itraconazole 200 mg daily resulted in an excellent response after 5-week treatment, leading to milder erythema, warmth and burning sensation, shorter duration, and fewer relapses. The treatment continued for 6 months and then itraconazole was decreased to 100 mg daily for another 6 months until it was stopped, with maintenance of good conditions. In 3 months of follow-up after the treatment ceased, the patient had only 7 to 8 attacks over 10 days presenting as tolerable erythema that lasted for less than 10 min and relieved spontaneously, with absence of warmth and no need of treatment. We considered the patient to be a variant of erythermalgia rather than a red ear syndrome. The results showed that erythermalgia might involve the ears alone and itraconazole might be a potential agent for its treatment.